حساب النسبة بين كمية الرواسب الناتجة من الانجراف المائي للتربة وكمية الرواسب المنقولة في نهر زغارو - حسن عز الدين; حماد منذر; اسماعيل كنان (Latakia University Journal -Engineering Sciences Series, 2014)
يُعدُّ الانجراف المائي أحد أبرز أشكال انجراف التربة وأكثرها خطورة, وخاصةً في المنطقة الساحلية حيث تهطل الأمطار بكميات كبيرة, وينتج عن ذلك جرف أطنان من التربة تنتقل بدورها إلى مجاري الأنهار, فيترسب جزء منها في هذه المجاري وجزء آخر في بحيرات السدود المُقامة عليها والباقي في البحار التي تصبّ فيها. تهدف الدراسة إلى حساب النسبة بين كمية الرواسب الناتجة من الانجراف المائي للتربة وكمية الرواسب المنقولة في نهر زغارو والتي تصل إلى بحيرة سد 16 تشرين, واقتراح الحلول المناسبة للتقليل من كميات هذه الرواسب والتخفيف من تأثيرها السلبي. تضمنت هذه الدراسة استنتاج خواص الحوض الساكب لنهر زغارو باستخدام برنامج نمذجة المياه ((WMS 7.1 , وكذلك حساب الكمية الإجمالية للرواسب الناتجة من الانجراف المائي للتربة في منطقة البحث باستخدام المعادلة العامة لفقد التربة , كذلك تضمنت قياس كميات الرواسب المنقولة في المياه وذلك بوساطة أجهزة قياس مُستخدمة عالمياً, قُمنا بتصنيعها لإجراء هذه التجارب. توصلت الدراسة إلى أن كمية الرواسب السنوية المُقاسة والمنقولة في مياه نهر زغارو تُعادل , وتُشكّل هذه الكمية 36% من الكمية الإجمالية السنوية للرواسب الناتجة من الانجراف المائي للتربة والتي تُعادل , وهي تُشكّل القيمة الفعلية للرواسب التي تصل إلى بحيرة سد 16 تشرين عن طريق مياه النهر, الأمر الذي يؤدي إلى تناقص الطاقة التخزينية لبحيرة السد, وهذا يستدعي إيجاد الحلول المناسبة من أجل التقليل من هذه الكمية والتخفيف من تأثيرها السلبي. Water erosion is considered one of the most prominent and dangerous forms of soil erosion, especially in the coastal region, where it rains in large quantities. Consequently, this results in sweeping away tons of soil into the river streams; some of this will be deposited in the rivers, some in the dam lakes constructed on these rivers, while the rest will be deposited in the sea into which rivers flow. The aims of this study are to calculate the ratio between the amount of sediments related to water erosion of the soil and the amount of the sediments transported in Zgaro River which reach the lake of 16 Tishreen Dam, and to suggest the appropriate solutions which will insure reducing the sedimentation rate and its correlated negative impacts. This study demonstrates the characteristics of the watershed of Zgaro River using Watershed Modeling System (WMS 7.1), and also the calculation of the total amount of sediments related to water erosion of the soil in the area of study, applying the Universal Soil Loss Equation (USLE). The amount of sediments transported by water was also calculated using internationally recognized measuring devices. These devices were manufactured for the purpose of this study. A total of 24886 tons of transported sediments was measured in Zgaro River, constituting 36% of the total annual amount of 69401 tons of sediments resulting from water erosion of the soil. This value comprises the actual amount of sediments deposited in the lake of 16 Tishreen Dam, which is then transported through the river stream. Consequently, this sedimentation has resulted in a downward trend of the reservoir capacity of the dam lake. These findings require feasible solutions to reducing the rate of sedimentation and its correlated negative impacts.